Tourist Narratives on Authenticity of Experience at Agro-tourism Destinations: A Phenomenological Study from an Eco-Spiritual Perspective at Sukomakmur Agrotourism - Nina Mistriani; John J. O. I. Ihalauw; Sony Heru Priyanto (Brilliant International Journal Of Management And Tourism, 2025)
This phenomenological study explores tourists' narratives and perceptions regarding the authenticity of experiences at Sukomakmur Agrotourism, Magelang, through an eco-spiritual lens. Agrotourism has evolved beyond agricultural education to encompass cultural, spiritual, and ecological dimensions, yet empirical studies on how tourists narrate authenticity in Indonesian agrotourism contexts remain limited. Using in-depth interviews with 15 tourists and participatory observation over three months (July-October 2025), the research employed interpretative phenomenological analysis to identify emerging patterns in tourists' authentic experiences. The research reveals that authenticity is interpreted through three interconnected dimensions: physical authenticity manifested through natural landscape and farming activities, cultural authenticity expressed through local wisdom and community interactions, and spiritual authenticity experienced through contemplative moments and transcendental connection with nature. Tourists describe experiencing profound connectedness, personal reflection, and transformative insights influenced by local wisdom and the religious-cultural milieu. The integration of eco-spiritual values significantly enhances tourist experience quality, creating memorable and meaningful encounters. The findings suggest that integrating eco-spiritual values can be a distinguishing element for sustainable agrotourism development, offering theoretical contributions to authenticity literature and practical guidance for destination management in creating transformative tourism experiences.